Imitatio Christi The Poetics of Piety in Early Modern England - Perry, Nandra (University of Notre Dame Press, 2014)
"In Imitatio Christi: The Poetics of Piety in Early Modern England, Nandra Perry explores the relationship of the traditional devotional paradigm of imitatio Christi to the theory and practice of literary imitation in early modern England. While imitation has long been recognized as a central feature of the period's pedagogy and poetics, the devotional practice of imitating Christ's life and Passion has been historically regarded as a minor element in English Protestant piety. Perry reconsiders the role of the imitatio Christi not only within English devotional culture but within the broader culture of literary imitation. She traces continuities and discontinuities between sacred and secular notions of proper imitation, showing how imitation worked in both contexts to address anxieties, widespread after the Protestant Reformation, about the reliability of "fallen" human language and the epistemological value of the body and the material world. The figure of Sir Philip Sidney-Elizabethan England's premier defender of poetry and internationally recognized paragon of Christian knighthood-functions as a nexus for Perry's treatment of a wide variety of contemporary literary and religious genres, all of them concerned in one way or another with the ethical and religious implications of imitation. Throughout the Elizabethan and early Stuart periods, the Sidney legacy was appropriated by men and women, Catholics and Protestants alike, making it an especially useful vehicle for tracing the complicated relationship of imitatio Christi to the various literary, confessional, and cultural contexts within and across which it often operated. Situating her project within a generously drawn version of the Sidney "circle" allows Perry to move freely across the boundaries that often delimit treatments of early modern English piety. Her book is a call for renewed attention to the imitation of Christ as a productive category of literary analysis, one that resists overly neat distinctions between Catholic and Protestant, sacred and secular, literary art and cultural artifact. "In Imitatio Christi: The Politics of Piety in Early Modern England, Nandra Perry explores the significance of imitatio Christi in the early modern English humanist tradition. In so doing, she reveals the tradition to be nothing less than a way to think, an organization for one's way in the world. She exposes the seriousness of religious thought in this period and the ways in which previous scholarship has limited our understanding by trying to graft authentic religious gestures onto anachronistic, secular divides." -Ken Jackson, Wayne State University "--